Poetry as embodied experience: the pragmatist aesthetics of Muriel Rukeyser's The Life of Poetry. Issue 7 (9th August 2018) - Gander, Catherine
ABSTRACT: This essay reads Muriel Rukeyser's The Life of Poetry (1949) as a vital account of pragmatist aesthetics in the vein of John Dewey's Art as Experience (1934). It argues that Rukeyser's treatise is an exercise in embodied cultural experience that draws upon the key pragmatic aesthetic tenets of pluralism and naturalism – i.e. the understanding that knowledge is derived from a living organism's mind–body interaction with its environment. Further, it explores Rukeyser's understanding that 'aesthetics', as contemporary philosopher Mark Johnson has argued, must move beyond the compartmentalised study of art and its a/effects to 'become the basis of any profound understanding of meaning and thought … to explore how meaning is possible for creatures with our types of bodies, environments, and cultural institutions and practices'. Highlighting recent studies in neuroscience, cognitive linguistics, and philosophy of embodied mind that are grounded in pragmatism, this essay demonstrates Rukeyser's foresight in constructing a cross-disciplinary, multivalent aesthetics of human meaning-making that anticipated such advances by decades. The Life of Poetry suggests a practical philosophy of the art of living that breaks down the traditional binaries of mind/body, science/art, self/other by positioning poetry pluralistically to encompass the social and personal potentialities of embodied human experience.